IMPACT OF THE METEOROLOGICAL RADIO PARAMETER PRECIPITATION INTENSITY ON MILLIMETRIC WAVE COMMUNICATIONS - Vladimir Manuel Conde, Williams; Pérez Garlobo, Lanyer (Telemática, 2024)
The country's efforts to develop and sustain telecommunications infrastructure in order to achieve greater access to broadband require the planning and design of microwave networks to ensure the transport of the new emerging services. In the millimeter band where some of these systems operate, precipitation in the form of rain is the main factor degrading the radio link. Therefore, it is necessary to evaluate the impact of the radiometeorological parameter "rainfall intensity" (R0.01) on the radiocommunication systems in the particular conditions of Cuba. Currently, the calculation of attenuation due to rainfall in the Fixed Service Terrestrial Radio Links (RESF), Satellite Radiocommunication Systems (SRCS) and others, only considers macro-scale values of the radiometeorological parameter, which influences the maximum distance of the links. In this sense, the impact of precipitation in the form of rain on the radiocommunications systems located in the study region, which includes the provinces of Artemisa, Havana and Mayabeque, is evaluated.